Pengaruh mekanisme good corporate governance terhadap kinerja perbankan dengan manajemen risiko sebagai variabel intervening - Agus Setiawaty (Faculty of Economics and Business Mulawarman University, 2016)
This study aimed to examine the effect of Good Corporate Governance (GCG) on risk management and the performance of banks in Indonesia. This study measures the extent of the implementation of corporate governance mechanisms in helping run the important managerial functions so as to reduce the risks faced and improve banks performance. Samples are banks listed in Indonesia Stock Exchange 2012-2014 period account to 90 sample observations. GCG in this study was measured by a composite score of the elements of governance, risk management is measured by a composite score of some of the bank's risk while the banks' performance is measured by return on assets (ROA). The data were analyzed using simple linear analysis is performed three times to find the direct and indirect influence of variables on corporate governance, risk management, and performance. The results showed that the risk management role as an intervening variable. The analysis showed that the mechanism of GCG has a significant negative effect on banks risk, in this case low risk showed a good risk management . In addition , GCG also has a significant positive effect on performance while the low risk (good risk management ) has a significant negative effect on performance ( performance improvement )Keywords: good corporate governance, risk management, performance